INNOVATIVE METHODS FOR DEVELOPING ENDURANCE IN YOUNG WRESTLERS (Innovate Conferences, 2025)
This article explores innovative methods for developing endurance in young wrestlers. The study emphasizes the importance of endurance as a key physical quality that directly affects the technical and tactical performance of athletes. Modern training technologies, including interval training, functional exercises, and the use of digital monitoring tools, are analyzed as effective means of improving aerobic and anaerobic endurance. The paper also highlights the role of individualized training programs and recovery strategies in optimizing the athletic performance of young wrestlers. The findings can serve as a methodological basis for coaches and physical education specialists in enhancing the overall preparation of young athletes.